Correction: Recovery from acute hypoxia: A systematic review of cognitive and physiological responses during the 'hypoxia hangover'. - David M Shaw; Peter M Bloomfield; Anthony Benfell; Isadore Hughes; Nicholas Gant (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0289716.].